Complementary Therapy for Anxiety of Pregnant Women in the Era of the Covid-19 Pandemic: Literature Review - Abidin, Zainal; Rahmawati, Primasari Mahardika; Safatullah, Muhammad Akhsal Dias (Universitas Bondowoso, 2022)
Introduction: Anxiety in pregnant women can cause dangerous stimulation of uterinecontractions, as a result of this condition pregnant women will have a negativeimpact, can increase blood pressure of pregnant women which can triggerpreeclampsia, premature babies, and even miscarriages in pregnant women. Theselection of interventions that can be done in reducing anxiety levels in pregnantwomen is by doing complementary therapies in the form of acupressure,aromatherapy, and 5 finger hypnosis Method: This study uses a Literature Review bysearching for journal articles conducted in November 2021 – April 2022 on theGoogle Scholar, Pubmed and Science Direct databases, with the keywords(Acupressure) or (Aromatherapy). ) or (5 finger hypnosis) and (anxiety) and(pregnant women). Result: The results obtained were 10 journal articles in accordance withthe inclusion criteria using the Quasi Experimental method as many as 6 journalarticles and a Randomized Controlled Clinical Trial as many as 4 journal articlesusing English and Indonesian Conclusion:The complementary therapy of acupressure, aromatherapy, and 5 fingerhypnosis is an easy, inexpensive, and can be done independently by pregnantwomen who experience anxiety, if done regularly and in accordance withcomplementary therapy procedures. Health services can apply complementarytherapies to pregnant women who experience anxiety and can be used by thecommunity as several forms of therapy in reducing anxiety in pregnant women withacupressure therapy, aromatherapy, and 5 finger hypnosis.